2014
DOI: 10.1155/2014/718702
|View full text |Cite
|
Sign up to set email alerts
|

Damage Assessment of Two-Way Bending RC Slabs Subjected to Blast Loadings

Abstract: Terrorist attacks on vulnerable structures and their individual structural members may cause considerable damage and loss of life. However, the research work on response and damage analysis of single structural components, for example, a slab to blast loadings, is limited in the literature and this is necessary for assessing its vulnerability. This study investigates the blast response and damage assessment of a two-way bending reinforced concrete (RC) slab subjected to blast loadings. Numerical modeling and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…where σ 0 is the yield stress under static loading, ε is the current strain rate and C = 40 s −1 and p = 5 are the strain rate parameters, as presented by Jia et al [43]. The strain rate strength enhancement of CFRP is not considered in this study due to its insignificance when compared to concrete and steel, as shown by the experimental results presented by Kimura et al [44], who have tested a series of unidirectional CFRP specimens at different strain rates and observed no influence in the tensile strength.…”
Section: Strain Rate Effectsmentioning
confidence: 99%
“…where σ 0 is the yield stress under static loading, ε is the current strain rate and C = 40 s −1 and p = 5 are the strain rate parameters, as presented by Jia et al [43]. The strain rate strength enhancement of CFRP is not considered in this study due to its insignificance when compared to concrete and steel, as shown by the experimental results presented by Kimura et al [44], who have tested a series of unidirectional CFRP specimens at different strain rates and observed no influence in the tensile strength.…”
Section: Strain Rate Effectsmentioning
confidence: 99%
“…Jiaming Xu and Yong Lu [28] stated that the former leads to an effective break-up of the slab along the shear failure line, while the latter eventually results in the reinforcing bars being pulled through in the concrete, which effectively eliminates the reinforcement effect and causes the collapse of the slab. Haokai et al [29] observed that the damage degree is directly affected by the explosive weights and positions. Also, it was observed that when the explosive weight is increased or the explosive standoff distance is decreased, the damage degree would increase.…”
Section: Literature On the Numerical Studiesmentioning
confidence: 99%
“…According to [10], the collapse modes of masonry walls that are exposed to blast actions may include flexural failure, direct shear failure, and flexural-shear failure. Collapse modes are further discussed in this section and elaborated in the analysis section of this article.…”
Section: Introductionmentioning
confidence: 99%